APPLICATION OF INDIGENOUS KNOWLEDGE SYSTEMS IN CLIMATE SMART AGRICULTURAL PRACTICES BY SMALLHOLDER FARMERS IN ISINGIRO DISTRICT, SOUTH WESTERN UGANDA - Wycliffe Tumwesigye, Tesfaye Lemma Tefera, Bobe Bedadi, Majaliwa Mwanjalolo Jackson-Gilbert & Petros Chavula (Chelonian Research Foundation, 2023)
Indigenous knowledge Systems (IKS) is widely applied in agronomy to enhance crop productivity and boost smallholder farmers’ food and income security globally. The study aimed at the documentation of the IKS options used in climate smart agriculture by smallholder farmers in meteorological drought vulnerable sub counties in Isingiro District, South Western Uganda. Focus group discussions of 18 men and 18 women aged between 30-70 years old and six key informants’ interviews were conducted in six selected Sub Counties of Isingiro District, South Western Uganda. Data was tested and validated by 12 agricultural experts. Results show that practices that were ranked rational (4) in cropping systems include: Site selection to match particular crops; Selection of climate resilient seed and early maturing varieties, water retention ditches, Mulching, application of organic fertilizers, selection of tolerant banana varieties for the area, early planting to avoid harsh environmental conditions, crop rotation, planting maize in lines, intercropping and diversification of agriculture. Those practices ranked high as being rational in the prediction of drought include: increased flowering of Bidens gratii sharff sp (ehoongwa), increased population of butterflies, quick and sudden movement of dark clouds, much coldness in the morning, much dew formation in the morning and scanty rains (muyaaya). IKS practices ranked high and rational (4) in predicting rainfall include: high temperature and the appearance of dark clouds in the atmosphere. Indigenous knowledge Systems are valuable in weather forecasting and climate change adaptation and mitigation. IKS are precursor for scientific knowledge and can guide science to do further investigation and expand on the knowledge database. Keywords: Indigenous Knowledge Systems, climate smart agriculture, soil water conservation, climate change mitigation, food security, smallholder farmers’ livelihoods